Dinamika Gerakan Sarekat Islam (SI) Cirebon dalam Kongres Al- Islam I 1922 - Imas Emalia (Buletin Al-Turas, 2008)
The study of islamic movement in Indonesia during the Dutch colonization left some problematic issues for the development of the after-independent islamic educational system inIndonesia. The first Al-Islam congress in Cirebon, which was held by Sarekat Islam (SI), was intended to underline several problems faced by the Indonesian Muslims at that time, to flourish Indonesian unity, and to recommend the Colonial government to abolish the Teachers' Act in 1905.On the contrary, since 1932 the Ducth Co lonial government issued Act on unauthorized schools (De Wilde Scholen Ordonantie) that legalize the government to eliminate schools run by Nationalist or Muslim Movements which were considered anti- government policy and unwilling to corporate withthe government.